2011
DOI: 10.1097/qad.0b013e328347f9d4
|View full text |Cite
|
Sign up to set email alerts
|

Non-AIDS-defining events among HIV-1-infected adults receiving combination antiretroviral therapy in resource-replete versus resource-limited urban setting

Abstract: Objective To compare incidence and distribution of non-AIDS-defining events (NADEs) among HIV-1-infected adults receiving combination antiretroviral therapy (cART) in urban sub-Saharan African versus United States settings. Design Retrospective cohort analysis of clinical trial and observational data. Methods Compared crude and standardized (to US cohort by age and sex) NADE rates from two urban adult HIV-infected cART-initiating populations: a clinical trial cohort in Gaborone, Botswana (Botswana) and an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 34 publications
0
51
1
Order By: Relevance
“…26,27 In this current analysis, the reported incidence of non-AIDS events was low, with no difference recorded between study groups. Serious adverse events possibly attributable to anti-retroviral treatment were also infrequent.…”
Section: Discussionmentioning
confidence: 52%
“…26,27 In this current analysis, the reported incidence of non-AIDS events was low, with no difference recorded between study groups. Serious adverse events possibly attributable to anti-retroviral treatment were also infrequent.…”
Section: Discussionmentioning
confidence: 52%
“…Renal failure accounted for 4 of 18 (22%) events in Tennessee versus 6 of 25 (25%) in Botswanna, with similar incidence rates (2.4 vs. 3.0 per 1,000 person-years, in Tennessee and Botswanna, respectively) [38]. Together, these studies describe a complex, and as yet an incomplete picture among sub-Saharan Africans living with HIV.…”
Section: African Ancestry and Kidney Diseasementioning
confidence: 91%
“…Nutritionappears to play a role in the development of non AIDS defining illnesses in HIV patients on long term HAART as a study by Wester et al (Wester et al, 2011) reported an increased incidence of non AIDS defining illnesses in an African Cohort especially among the overweight adults. With HIV and nutrition being strongly related, the nutritional implications in the prognosis and management of HIV infection especially in developing countries is highlighted by the associated prevalence of nutrient deficiencies established early in the course of HIV infection coupled with the fact that micronutrient deficiencies are more likely to occur among residents of developing countries like Nigeria; that is ranked the 3 rd highest with respect to absolute numbers of stunting with annual losses of US$1.5 billion in Gross Domestic Product due to vitamins and mineral deficiencies (Montaner et al, 1998; United Nations Children's Fund (UNICEF),2009; World Bank; Jiang et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…A Swiss Cohort study observed that while the incidences of AIDS defining events are reducing, the non AIDS defining events are increasing with aging and as a consequence, the non AIDS related diseases are now becoming major causes of health concern in HIV patients on long term HAART with associated morbidity and mortality [Hasse et al, 2011;The Antiretroviral Therapy Cohort Collaboration (ART-CC writing committee);2010]. This particularly appears to be constituting a significant problem in sub Saharan Africa and therefore requires that monitoring, prevention and treatment should be a critical component of care in resource limited regions (Wester et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation